PENGEMBANGAN BAHAN AJAR PKN BERBASIS NILAI KEBERSAMAAN MASYARAKAT MINANGKABAU UNTUK MEMBANGUN KARAKTER BANGSA PESERTA DIDIK SEKOLAH DASAR - Hasmai Bungsu Ladiva; Rafhy Febryan Putera; Yesi Anita (Universitas Negeri Padang, 2018)
This study aims to develop a value-based teaching material for Citizenship Education (PKn) together with the local wisdom of the Minangkabau community to build the national character of the fifth grade students of Elementary School. The research conducted is research and development with the ADDIE research model which is an acronym in English from the stages of analysis, design, development, implementation, and evaluation. By participating in the development stage of the ADDIE model, teaching material development is carried out by combining the values of togetherness found in the local wisdom of the Minangkabau community in a single unit of learning material. Data obtained from the validation of teaching materials, classroom learning practices, and the effectiveness of learning from student learning outcomes. The results of this study indicate that the development of Pkn teaching materials based on the values of togetherness of the Minangkabau community has been successfully carried out based on data on the validity, practicality, and effectiveness of teaching materials in learning in Class V of Elementary School.Keywords: Development Research, Minangkabau, PKn, SD Togetherness Value.